2020
DOI: 10.21037/jtd-20-3410
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enteral nutrition support combined with enhanced recovery after surgery on the nutritional status, immune function, and prognosis of patients with esophageal cancer after Ivor-Lewis operation

Abstract: Background: Esophageal cancer (EC) with a high incidence of malnutrition is a highly malignant digestive tract tumor. We investigated the effect of enteral nutrition (EN) support combined with enhanced recovery after surgery (ERAS) on the nutritional status, immune function, and prognosis of patients with EC after Ivor-Lewis operation.Methods: One hundred patients were randomly divided into the observation group (n=42) and the control group (n=58). The patients in observation group were treated with EN combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Patients who undergo esophagectomy always suffer from weight loss and malnutrition due to alteration of the dietary pattern. Previous studies have reported that enteral nutrition support could not only improve patients’ nutritional status and immune function but also preserve the skeletal muscle mass [ 30 , 31 ]. Family enteral nutrition was reported to reduce the risk of malnutrition and incidence of complications after esophagectomy [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients who undergo esophagectomy always suffer from weight loss and malnutrition due to alteration of the dietary pattern. Previous studies have reported that enteral nutrition support could not only improve patients’ nutritional status and immune function but also preserve the skeletal muscle mass [ 30 , 31 ]. Family enteral nutrition was reported to reduce the risk of malnutrition and incidence of complications after esophagectomy [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…[63][64][65] In addition, there is more focus on preoperative malnutrition and impaired physical capacity, which are shown to be negative prognostic factors for postoperative complications in this meta-analysis. 66 Intra-and postoperative care are also being standardized in ERAS protocols (e.g., fluid therapy, opioid-sparing analgesia). 67 The reduction of postoperative complications is important because complications are associated with reduced overall survival.…”
Section: Perioperative Carementioning
confidence: 99%
“…Esophageal cancer is a highly malignant digestive tract tumor, ranking the 5th among the causes of cancer-related death in worldwide [ 14 ]. Although the diagnostic techniques and treatment methods for esophageal cancer have been continuously improved recent decade, the overall survival status of esophageal cancer patients is still unsatisfactory due to the characteristics of early invasion and distant metastasis [ 15 ].…”
Section: Discussionmentioning
confidence: 99%